Synergistic and Antagonistic Effects of Biogenic Silver Nanoparticles in Combination With Antibiotics Against Some Pathogenic Microbes - Aabed, Kawther; Mohammed, Afrah E. (Frontiers in Bioengineering and Biotechnology, 2021)
The latest advances in green nanoparticle synthesis have preserved natural and non-renewable resources and decreased environmental pollution. The current study was designed to evaluate silver nanoparticles (AgNPs) fabricated using aqueous extracts of two medicinal plants, Anastatica hierochuntica L. (Kaff Maryam) and Artemisia absinthium. The phytochemicals were detected by Fourier-transform infrared spectroscopy (FTIR) and Chromatography/Mass Spectrometry (GC-MS). The effects of the AgNPs on Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, and Candida albicans as well as the cytotoxicity against MDA-MB-231 cells were examined. The synergistic and antagonistic effects of the biogenic AgNPs in combination with standard antibiotics against several microbes were also investigated. The ability of the plant extracts to transfer silver ions to AgNPs was measured via dynamic light scattering, zeta potential measurement, and transmission electron microscopy. The most sensitive microbes to AgNP treatment were examined via scanning electron microscopy to assess morphological changes. Biogenic AgNPs showed significant antibacterial effects against most of the tested microbes and significant cytotoxicity was noted. Polysaccharides, proteins and Phenolic compounds are likely involved in AgNP biosynthesis since hydroxyl groups and amides were detected via FTIR as well as GC-MS. This study confirmed that plant-based AgNP fabrication with AgNO3 as the Ag (I) delivering salt can be an economical and practical approach for large-scale production of particles with antimicrobial and cytotoxic potential. The synergistic effects of biogenic AgNPs in combination with some antibiotics support their potential as a safe therapeutic for bacterial infections because they are capped with organic biomolecules.